Tingkat Kepercayaan, Kualitas Layanan, Brand Preference dan Minat Menabung - I Kadek Andy Asmarajaya; Ida Bagus Raka Suardana (Universitas Pendidikan Nasional, 2018)
ABSTRACTThe purpose of this research is to know the influence of trust and quality of service to brand preference and influence of trust level, service quality and brand preference to interest of saving. The design of this research is quantitative, is the relationship of causality between variables. The research was conducted at LPD Kelan Village Traditional. Data collection techniques used questionnaires to 170 customers. Data were analyzed by data analysis technique Structure Equation Modeling with AMOS program. The results showed that there was a significant positive influence between the level of trust on brand preference. This means that if the level of public confidence increases then the interest of the community to save Kelan Traditional Village also increased significantly. There is a positive influence pattern of Service Quality on brand preference. This means that if the quality of service increases the interest of saving society also increased significantly. There is a significant positive influence between the level of trust on the interest of saving society. This means that if the level of public confidence increases then interest in saving the Kelan traditional village also increased significantly. There is a positive influence pattern of service quality to the interest of saving Kelan Customary Village community. This means that if the quality of LPD Kelan Village Traditional increased then the interest of saving the community of LPD Kelan Village Traditional also increased significantly. There is a positive and significant influence between the brand preference on the interest of saving the society of Kelan Traditional Village. This means that if the brand preference increases then the interest of saving Kelan traditional community also increased significantly.